2010
DOI: 10.1371/journal.pone.0011448
|View full text |Cite
|
Sign up to set email alerts
|

CD40 Ligand (CD154) Incorporated into HIV Virions Induces Activation-Induced Cytidine Deaminase (AID) Expression in Human B Lymphocytes

Abstract: Most AIDS-associated non-Hodgkin's lymphoma (AIDS-NHL) arises from errors in immunoglobulin heavy-chain gene (IgH) class switch recombination (CSR) or somatic hypermutation (SHM), events that occur in germinal center (GC) B cells and require the activity of activation induced cytidine deaminase (AID). Several oncogenic viruses (EBV, HCV, HPV) can induce AID gene (AID) expression, and elevated AID expression is seen in circulating lymphocytes prior to AIDS-NHL diagnosis. Here, we report that HIV produced in per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 38 publications
4
48
1
Order By: Relevance
“…be noted that a recent work by Epeldegui and colleagues reported the physical presence of host CD40L on the surface of virions circulating in the plasma from two out of three HIV-1-infected persons (18). Therefore, our observations validate this report and render experiments aimed at monitoring the biological activity of virus-associated CD40L highly important.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…be noted that a recent work by Epeldegui and colleagues reported the physical presence of host CD40L on the surface of virions circulating in the plasma from two out of three HIV-1-infected persons (18). Therefore, our observations validate this report and render experiments aimed at monitoring the biological activity of virus-associated CD40L highly important.…”
supporting
confidence: 87%
“…From crucial regulators of CD40/NF-B signal transduction and apoptosis, such as TRAF1 and A20, to adhesion molecules (ICAM-1), costimulation molecules (CD80), and cytokines (LTA and LTB) associated with B-cell immune functions, to negative-feedback-loop transcripts (IB␣) and essential components involved in antibody gene recombination and hypermutation (AID), the resulting portrait is unequivocally akin to an activated, proliferating, and/or differentiating B-cell phenotype. The present findings extend beyond the study made by Epeldegui and coworkers who have assessed the capacity of CD40L-bearing HIV-1 particles to induce the activation of a single gene in B cells, namely, AID (18).…”
supporting
confidence: 76%
“…Indeed, abnormal antibody responses and B cell phenotypes have been reported from aberrant gp120 and Nef signaling (24,25), and IL-10 and CD154 can be either helpful or deleterious in combination with different factors (26). Moreover, HIV exploits these interactions and hijacks the CD40 signaling pathway to induce alterations in B cell phenotype and function (27). Thus, the nature of the helper T cell response would be expected to influence antibody response to particular viral antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Host cell derived CD40 ligand (CD40L) that are incorporated into HIV-1 virions are capable of binding to CD40 expressed on B cells and promoting class switch [15]. In a recent study, Epeldegui et al [16] investigated binding of host CD40L in HIV-1 virions to CD40 on B-cell surface and the effect on expression of AID in B cells. They demonstrated that HIV-1 virions produced in 293 T cells expressing CD40L, but not virions produced in 293 T cells without CD40L expression, stimulated AID transcription, resulting in elevated AID protein levels.…”
Section: Regulation Of Antibody Class Switchingmentioning
confidence: 99%